Sur la convergence de l'intégrale de Laplace—Stieltjes type - Abdrakmanov, V. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Г. Абдрахманов. О сходимости интеграла типа Лапласа—СтилтьесаV. Abdrakmanovas. Laplaso—Stiltieso tipo integralo konvergencijos klausimu